Fractionation of Mastic Gum in Relation to Antimicrobial Activity - Mohammad Sharif Sharifi; Stuart Loyd Hazell (MDPI AG, 2009)
Mastic gum is a viscous light-green liquid obtained from the bark of Pistacia lentiscus var. chia. which belongs to the Anacardiaceae family. The gum has been fractionated to investigate the antimicrobial activity of the whole gum and its fractions against various strains of Helicobacter pylori. The polymeric gum fraction was separated from the essential oil and the resin (trunk exudates without essential oil) to assess and compare the anti-H. pylori activity of the polymer fraction against lower molecular weight fractions, the gum itself and masticated gum. The polymer fraction was also oxidized and assessed for antimicrobial activity.